Potencialidades da farinha integral do milheto (Pennisetum glaucum L.) e aplicação em pães sem glúten: efeito no comportamento nutricional e tecnológico - Herculano, Leiliane da Fonseca Lima (2023)
Pearl millet (Pennisetum glaucun L.) is a crop adapted to agricultural conditions in Brazil, however its national production is destined only for animal feed and vegetable cover (no- tillage). One of the reasons for non-consumption by humans may be related to the lack of knowledge about the nutritional benefits and types of products that can be made with flour, so millet has the potential to become a new staple food, especially in times of hunger. This study aimed to emphasize the important nutritional and technological potential of whole millet flour for human consumption in bakery products, awakening food industries and consumers to its benefits, especially for celiacs. Whole millet flour was produced and analyzed for physical- chemical composition, mineral profile, functional properties, bioactive compounds, color, granulometry, scanning electron microscopy (SEM) and toxicity, then 2 gluten-free bread formulations were produced, with FP being the standard formulation and FM being the formulation with 25% whole millet flour, and evaluated for specific volume, texture, crumb color and physical-chemical characterization. Whole millet flour was characterized as a flour rich in total and insoluble fiber, with a high content of proteins, lipids and minerals (P, Mg, Fe and K). The bioactive compounds, total phenolics and total flavonoids, were identified, considering that phenolic acids were detected in high amounts, showing potential for application as an antioxidant. The characteristics of color (light, with yellow tones), granulometry and technological functional properties (with emphasis on water absorption index, water solubility and emulsifying activity) proved to be interesting for the use of flour as an ingredient for various applications in the food industry. food, mainly for the production of gluten-free bread. No acute toxicity was demonstrated for the microcrustacean Artemia salina, so the product proved to be safe for consumption. The proportion of 25% whole millet flour proved meeting the technological parameters, increasing the specific volume of breads and reducing color and firmness in the formulations, characteristics desired by consumers. The nutritional characterization presented a nutritious and healthy product option. It can be concluded that whole millet flour is an excellent option for the development of food products, especially gluten-free bread, with excellent characteristics to be presented as a new option for the market